2019
DOI: 10.1111/hsc.12848
|View full text |Cite
|
Sign up to set email alerts
|

Care workers under pressure – A comparison of the work situation in Swedish home care 2005 and 2015

Abstract: As in many Western countries, eldercare services in Sweden have changed dramatically over recent decades. Population ageing, ageing‐in‐place policies, pressures to contain costs and organisational reforms linked to New Public Management are challenging public home care. There is, however, limited knowledge about how the job content and working conditions have changed in the Swedish home care across this period. This article aims to analyse and compare the work situation in the Swedish home care in 2005 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
87
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(105 citation statements)
references
References 45 publications
1
87
0
Order By: Relevance
“…37e39 Research in the Swedish context has shown that the workload in HCS is increasing, with an increasing number of severely ill persons to care for and an increasing number of persons per staff member per day. 40 The schedules of HCS staff are full of tasks to be completed and with a general amount of time provided for the tasks, which likely results in a PCC approach being deprioritized simply due to a lack of time. This may also influence the health of staff, as Strandell 40 revealed that mental exhaustion and work-related problems among HCS staff are increasing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37e39 Research in the Swedish context has shown that the workload in HCS is increasing, with an increasing number of severely ill persons to care for and an increasing number of persons per staff member per day. 40 The schedules of HCS staff are full of tasks to be completed and with a general amount of time provided for the tasks, which likely results in a PCC approach being deprioritized simply due to a lack of time. This may also influence the health of staff, as Strandell 40 revealed that mental exhaustion and work-related problems among HCS staff are increasing.…”
Section: Discussionmentioning
confidence: 99%
“…40 The schedules of HCS staff are full of tasks to be completed and with a general amount of time provided for the tasks, which likely results in a PCC approach being deprioritized simply due to a lack of time. This may also influence the health of staff, as Strandell 40 revealed that mental exhaustion and work-related problems among HCS staff are increasing. Other research showed perceived job strain among staff because of their inability to deliver good enough care.…”
Section: Discussionmentioning
confidence: 99%
“…These reforms lead to new age management challenges that are primarily aimed at answering questions about how to formulate workload and working conditions so that these employees work efficiently for the organisation and, more importantly, not to lose organisational knowledge of those retiring. Research conducted by [1] shows that organisational reform of working conditions should meet the employment requirements of all employees with emphasis on those over the age of 50, given their tenure and organisational knowledge, as confirmed by a study by [2]. The research focused on conditions for the performance of managerial positions in the public sector, which would lead to the permanent retention of managers' ability to perform their positions.…”
Section: Introductionmentioning
confidence: 96%
“…This is the focus of age management, which targets all age groups of employees, and develops strategies to create a forward moving organisation focused on corporate goals. However, the age structure of the population and employment policy puts pressure primarily on retaining employees over the age of 50, and in many cases also lead to organisational reforms [1]. These reforms lead to new age management challenges that are primarily aimed at answering questions about how to formulate workload and working conditions so that these employees work efficiently for the organisation and, more importantly, not to lose organisational knowledge of those retiring.…”
Section: Introductionmentioning
confidence: 99%
“…omecare service work can be described as low-status, nonprofessional, and not seen as contributing to societal production (Aronson & Neysmith 1996;Keisu et al 2016;Strandell 2020). Yet, at the same time, this kind of work is an essential part of the welfare state and plays an important role in countries such as Sweden, Denmark, and Norway, where the societies lean towards a model where the state takes care of the elderly (Kamp et al 2013;Madsen 2018;Meldgaard Hansen 2016).…”
mentioning
confidence: 99%